Teaching the Seasons of the Year to Kindergarten Students Using Desktop Virtual Reality: A Comparative Study - Fokides, Emmanuel; Samioti, Antigoni (Qeios, 2023)
Teaching concepts related to the natural environment in early childhood education significantly impacts cognitive development and corrects misconceptions. Technological advancements have introduced innovative educational tools such as virtual reality (VR). Among the various forms of VR, desktop VR (dVR) is the most practical for use in a school setting, as it requires no specialized equipment other than computers. With this in mind, a project was implemented to examine the impact of a dVR application on kindergarten students' learning. A total of forty-five students participated in a within-subjects research design, studying the seasons of the year. The learning outcomes were then compared with those produced by conventional materials. Furthermore, students' feelings and attitudes were also analyzed. The results showed that when using the dVR application, students performed significantly better in terms of learning, immersion, motivation, enjoyment, and ease of use. Factors such as students' gender and prior knowledge did not have any significant effect. The study's implications for research and education are also discussed.